Ligand-controlled preparation and fundamental understanding of anisotropic gold nanostructures - Xia, Jing (2018)
In these decades, Au nanostructures have been demonstrated to be promising nanomaterials in catalysis, detection and biomedicine. The merit of these applications manly arises from the expression of properties with strong correlations to their shape and size. Thus, well control of Au nanostructures in shape and size is important in improving their properties and applications. To synthesize morphology-controlled Au nanostructures, well understanding of their growth mechanism is crucial. Therefore, the main objective of this thesis is to prepare anisotropic Au nanostructures and understand their growth mechanism behind. Colloidal growth of Au nanostructures has been exploring for decades via chemical reduction of AuCl4-. The intermediate process is very difficult to investigate during the fast reduction of Au3+ to Au0, and thus it is of importance to explore the slow reduction for study of intermediate process with a series of weak reducing agents possessing typical aldehyde groups (i.e., HCOH, HCOOH, HCONH2, HCOCH3 and HCON(CH3)2). The binding energies of Aun+ (n = 3, 1 and 0) to ligands are simulated to exhibit binding different affinities to starting, intermediate and final Au species. In an optimized slow reaction in which ligands show stronger binding affinities to Au+ than Au3+ and Au0, intermediate process that the formation and disproportionation of Au+ is demonstrated. For example, formic acid has much stronger binding affinity to Au+ than Au3+ so that intermediate Au+ is able to be captured during the slow reduction of Au3+. Upon the disproportionation of Au+ to Au0 and Au3+, the binding affinity of ligands to different Au facets and Au0 is crucial in controlling growth of anisotropic Au nanostructures. The adsorption of various ligands causes substantially decreased surface energies on different Au planes. There are much higher energies on {110} planes compared to the other two {111} and {100} planes with certain ratios in these energies, leading to morphological growth of Au nanoplates by various organic ligands. Meanwhile, ligands with stronger binding energies to Au0 have stronger effect in controlling the anisotropic growth of Au nanostructures. Furthermore, Ag, Pd and Pt nanosheets are successfully prepared via this facile synthetic method. In addition, using the as-prepared Au nanoplates as templates, ultrathin Au nanosheets with average thickness of ~1.5 nm and bimetallic nanostructures maintaining the plate-like shape are also produced.